For the Benefit of All : Fiscal Policies and Equity-Efficiency Trade-offs in the Age of Automation - Berg, Andrew (IMF Working Papers; Working Paper ;, 2021)
Many studies predict massive job losses and real wage decline as a result of the ongoing widespread automation of production, a trend that may be further aggravated by the COVID-19 crisis. Yet automation is also expected to raise productivity and output. How can we share the gains from automation more widely, for the benefit of all? And what are the attendant equity-efficiency trade-offs? We analyze this issue by considering the effects of fiscal policies that seek to redistribute the gains from automation and address income inequality. We use a dynamic general equilibrium model with monopolistic competition, including a novel specification linking corporate power to automation. While fiscal policy cannot eliminate the classic equity-efficiency trade-offs, it can help improve them, reducing inequality at small or no loss of output. This is particularly so when policy takes advantage of novel, less distortive transmission channels of fiscal policy created by the empirically observed link between corporate market power and automation.